Biosynthesis of Selenium Nanoparticle by Whole Cells of Saccharomyces boulardii and its Evaluation as Anticancer Agent - Patel, Navin; Kaler, Abhishek; Jain, Sanyog; Chand Banerjee, Uttam (Current Nanoscience, 2013)
Selenium is known to have cytoprotective role, which is important especially in reducing mortality due to cancer, a leading cause of death worldwide. The present work addresses synthesis and evaluation of selenium nanoparticles (SeNPs) as therapeutic alternative to conventional chemotherapeutic agents. Selenium nanoparticles were synthesized by an eco friendly method using whole cells of Saccharomyces boulardii. Parameters like culture age (stationary phase growth), cell mass concentration (100 mg/ml), temperature (35°C) and reaction time (72 h) were optimized to produce nanoparticle with controlled properties. Nanoparticles were recovered by alkali hydrolysis and subjected to UV-Vis spectroscopy, EDX (energy dispersive X-rays) analysis, electron microscopy, elemental analysis and size determination. Dynamic light scattering analysis reveals negative zeta potential value of 14.8 mV and PDI of 0.25. Experiments to prove possible involvement of sulfite reductase in nanoparticle formation has been carried out. Moreover, cytoprotective role of selenium nanoparticle has been shown by cell viability in MTT assay.
Keywords: Saccharomyces boulardii